A systematic review and meta-analysis reveal that Campylobacter spp. and antibiotic resistance are widespread in humans in sub-Saharan Africa. - Delfina F Hlashwayo; Betuel Sigaúque; Emília V Noormahomed; Sónia M S Afonso; Inácio M Mandomando; Custódio G Bila (PLoS ONE)
Introduction Campylobacter spp. are zoonotic bacteria that cause gastroenteritis in humans worldwide, whose main symptom is diarrhea. In certain cases, extra intestinal manifestations may occur, such as Guillain Barré syndrome. The bacteria cause severe diarrhea mostly in children and in immunocompromised individuals. This review aims to address the prevalence of Campylobacter spp. in humans in sub-Saharan Africa. It also aims to understand the impact of HIV in the prevalence, as well as to report data on antibiotic resistance and propose research priorities. Methods We followed PRISMA guidelines to find studies on the occurrence of Campylobacter spp. in humans in all countries from sub-Saharan Africa. Studies published between 2000 and 2020 were searched in PubMed, Cochrane Library, CINAHL, African Index Medicus, African Journals Online, Google Scholar and Science Direct. We have conducted a random-effect meta-analysis and calculated the proportion of resistant isolates to different antibiotics. Results and discussion We found 77 studies that described such occurrence in humans in 20 out of 53 sub-Saharan African countries. Campylobacter jejuni was the most prevalent species. Pooled prevalence was 9.9% (CI: 8.4%-11.6%). No major variations within the different sub-regions were found. Most studies reported Campylobacter spp. as the cause of diarrhea, mainly in children. Some studies reported the bacteria as a possible etiologic agent of acute flaccid paralysis and urinary tract infection. Campylobacter spp. presented a higher pooled prevalence in HIV infected patients, although not statistically significant. High proportions of resistant strains were reported for many antibiotics, including erythromycin and tetracycline. Conclusion Campylobacter spp. occur in sub-Saharan Africa, although information is scarce or inexistent for many countries. Research priorities should include investigation of the understudied species; extra intestinal manifestations; the impact of HIV infection and associated risk factors. Control strategies should be reinforced to contain the spread of this pathogen and drug resistance.